Spatial analysis of Forage Gropes production in Iraq for the period (2010-2020) - Alzubaidi, Amal (Al-Adab Journal, 2023)
The production of Forage Cropes has an important economic and industrial position at the local economic level and the general economy of the country, and in Iraq production faced many natural and human challenges, especially with the increasing demand for it locally, which required studying and analyzing the dimensions of the problem and its spatial and temporal variation.The study specialized in the most important fodder crops, which are (Alfalfa, Berseem, Forage Sorghum, Seed Mixtures) and the study included the productive governorates, namely (Baghdad, Wasit, Babil, Kerbala, Najaf, Qadisiyah, Missan, Thiqar, Muthanna, Basrah) and a time series that extended between (2010-2020).The study was built according to the literature of geographical scientific research from the presentation of the theoretical framework and analysis of the phenomenon data and the use of descriptive and inferential geographical quantitative analysis methods of data and variables of the phenomenon to reach realistic results and develop logical proposals. Cluster analysis was used to classify independent variables and their relationship to the dependent variable.The study reached a number of conclusions, the most important of which are:The results of the cluster analysis of the Alfalfa crop showed three groups: the first group, which is the most close group and includes the governorates of (Babil, Missan, Muthanna, Kerbala and Qadisiyah). The second group that follows includes the governorates of (Baghdad, Basrah, Najaf and Thiqar). While Wasit represents a different third group. As for the cluster analysis of Berseem, which showed three groups: the first group, which is the most close and includes the governorates of (Kerbala, Qadisiyah and Wasit), the second group, which includes the governorates of (Baghdad, Babil, Thiqar and Missan), while Najaf represents a different third group. As for the results of the cluster analysis of the Forage Sorghum, it showed three groups: the first group, which is the most close, and includes the governorates of Babil and Wasit. The second group includes Baghdad province only. While the province of Kerbala represents a different third group. As for the results of the cluster analysis of the crop of Seed Mixtures, it showed three groups: the first group, which is the most close group, and includes the governorates of (Baghdad and Babil). The second group includes the province of Kerbala only. While Wasit represents the third different group.